2014
DOI: 10.1371/journal.pone.0090740
|View full text |Cite
|
Sign up to set email alerts
|

Unforeseen Effects of Supplementary Feeding: Ungulate Baiting Sites as Hotspots for Ground-Nest Predation

Abstract: Despite the ubiquity and magnitude of food provision to wildlife, our understanding of its ecological effects and conservation implications is very limited. Supplementary feeding of ungulates, still one of the main paradigms of game management in Europe, occurs in natural areas on an enormous scale. We investigated the indirect effects of this practice on nest predation risk in the Polish Eastern Carpathians (Bieszczady Mountains). We hypothesized that the predators attracted to ungulate baiting sites would al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 43 publications
0
50
0
3
Order By: Relevance
“…Studies using artificial bird nests suggest increased predation of groundnesting birds adjacent to 'vulture restaurants' (Cortés-Avizanda et al 2009) and deer feeders (Cooper and Ginnett 2000), with a 30 % increase in the predation of artificial ground nests in close proximity to deer feeders in Poland (Selva et al 2014). Similarly, trials to quantify predation of artificial turtle nests showed that scavengers attracted to deer feeding stations resulted in a five-fold increase in predation rates on artificial nests (Hamilton et al 2002).…”
Section: Have Effects On Habitat Conditions and Non-target Species Bementioning
confidence: 99%
“…Studies using artificial bird nests suggest increased predation of groundnesting birds adjacent to 'vulture restaurants' (Cortés-Avizanda et al 2009) and deer feeders (Cooper and Ginnett 2000), with a 30 % increase in the predation of artificial ground nests in close proximity to deer feeders in Poland (Selva et al 2014). Similarly, trials to quantify predation of artificial turtle nests showed that scavengers attracted to deer feeding stations resulted in a five-fold increase in predation rates on artificial nests (Hamilton et al 2002).…”
Section: Have Effects On Habitat Conditions and Non-target Species Bementioning
confidence: 99%
“…, Selva et al. , Hanmer et al. ), particularly for bird species that do not directly benefit from the resource but may suffer the consequences of increased risks of nest depredation.…”
Section: Introductionmentioning
confidence: 99%
“…Here we consider supplemental feeding to include also baiting (i.e. feeding for the purpose of attracting or/and capturing wildlife), since in many areas (especially in Europe) feeding is often used simultaneously for several purposes (Kav č i č et al 2013, Selva et al 2014). Supplemental feeding is commonly used in wildlife management and conservation.…”
mentioning
confidence: 99%